2017
DOI: 10.21315/tlsr2017.28.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of a Molybdenum-reducing and Metanil Yellow Dye-decolourising Bacillus sp. strain Neni-10 in Soils from West Sumatera, Indonesia

Abstract: Abstrak: Satu bakteria penurun molibdenum dengan keupayaan baru untuk menyahwarna pewarna azo Kuning Metanil dilaporkan. Kondisi optimum untuk penurunan molibdenum adalah pada pH 6.3 dan pada suhu 34°C. Glukosa adalah penderma elektron yang terbaik. Keperluan-keperluan lain termasuklah kepekatan fosfat yang sempit di antara 2.5 dan 7.5 mM. Profil masa pengeluaran Mo-biru menunjukkan tempoh sela masa kira-kira 12 jam, jumlah maksimum Mo-biru dihasilkan pada kepekatan molibdat 20 mM dan pengeluaran maksimum pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
(103 reference statements)
2
28
0
Order By: Relevance
“…Based on previous studies, the phosphate concentration required is around 5 mM and lower for optimal Mo-reduction [13,15,18,23,28,[30][31][32][33][34][35][36][37]39]. The result of the present study showed that maximum concentration of phosphate also occurred at 5.0 mM.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionsupporting
confidence: 58%
“…Based on previous studies, the phosphate concentration required is around 5 mM and lower for optimal Mo-reduction [13,15,18,23,28,[30][31][32][33][34][35][36][37]39]. The result of the present study showed that maximum concentration of phosphate also occurred at 5.0 mM.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionsupporting
confidence: 58%
“…strain Zeid 14 and Burkholderia sp. strain NENI-11 could utilize acrylamide as a source of electron donor for reduction and were able to grow on media containing acrylamide, acetamide, and acetonitrile ( Mansur et al, 2016 ; Mohd et al, 2016 ). Enterobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…strain Saw-1 and Bacillus sp. strain Neni-12 could consume the pesticide coumaphos as an alternative carbon source for growth ( Sabullah et al, 2016 ; Rusnam and Gusmanizar, 2019 ). However, a previous study found that although some molybdenum-reducing bacteria can successfully utilize pesticides as a carbon source, those pesticides cannot be used as an electron donor for molybdenum reduction ( Sabullah et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, the only known Burkholderia genus able to reduce Mo is Burkholderia sp. strain Neni-11 (Mansur et al 2016) with an optimum pH of between 6.0 and 6.3. Having a wide range of optimum pH range for Burkholderia vietnamiensis strain AQ5-12 and Burkholderia sp.…”
Section: Discussionmentioning
confidence: 99%